Permainan Tradisional Bakiak Untuk Perkembangan Motorik Kasar Anak - Andan Firmansyah; Alifia Badriatul H; Kemala Fauzia; Listiawati Listiawati; Meida Bintari; Mutia Dwi M; Nendela Resta Angga Putri (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introducation: Bakiak game is one of the traditional games originating from West Sumatra which was born in the mid-1970s. This game tool is made of two thick sandal-shaped wooden planks that are about 125 cm long. On each board there are three or four rubber straps to tie the players' feet. Objective: the purpuse of this study was to determine the effectiveness of the traditionl bakiak game on the motordevelopment of elementary school children. Method: The method chosen is the type of Classroom Action Research (PTK) whic has four stages of procedure namely, planning, implementation (action), observaton (observation), reflection. Used in this research  are observation and documentation. Result: The result of  these observations indicate that gross motor development in children has not developed properly, especially when walking using clogs which requires a lot of training. This is the reason for researchers to observe again the gros motor development of children in the next stage. Conclusion: The conclusion of this research on traditional bakiak games on children's gross motor development is going according to plan. The series of activities from start to finish went well, the children and teachers were very enthusiastic and active in playing. This game has a  positive effect on the development of  gross motor skills and social development of children. There are very significant changes before and after the game